Effect of Exposure of Smartphone Use on Visually Evoked Potential (VEP) in Healthy Adults - Swapnil Bhirange1 , Alka Rawekar2 , Avinash Taksande3 , Komal Meshram4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aims: To assess and compare VEP parameter (amplitude and latency of P100) in healthy adults (MBBSstudents) using smartphone.Objectives:• To record P100 (latency, amplitude) in 1st year MBBS students using smartphone for less than threehours and for more than three hours after sunset• To record P100 (latency, amplitude) MBBS students using smartphone for duration of less than threeyears and for more than three years• To Compare P100 (latency, amplitude) 1st year MBBS students using smartphone for less than threehours and for more than three hours after sunset• To Compare P100 (latency, amplitude) MBBS students using smartphone for duration of less than threeyears and for more than three yearsSettings and Design: Neurophysiology Lab at the department of Physiology, JNMC, Sawangi (Meghe),Wardha.Method and Material: A cross sectional study was done in 50 healthy MBBS studentsfrom JNMC.Results: There is significant difference in the mean values of P100 latencies of right and left eye and in themean values of P100 amplitude of right and left eye in individuals with exposure of less than three and morethan three hours per day after sunset.Conclusions: We conclude that nocturnal use of mobile phones especially in the bright light exposes anindividual to the blue light resulting in various deleterious effects.